Reconsidering Rag-i Bibi: Authority and audience in the Sasanian East. Issue 2 (October 2019) - Levine, Evan I.; Plekhov, Daniel
Abstract : The Sasanian rock-cut relief of Rag-i Bibi, located in northern Afghanistan, offers a unique opportunity to reconsider issues of audience, memory, and power in rupestral art. Found over 1, 000 kilometers east of the nearest attested Sasanian rupestral relief, Rag-i Bibi is geographically and iconographically distinct, displaying elements of local subject matter, artistic style, and political symbolism. Through comparison to reliefs in the Sasanian west and local artistic traditions, the stylistics and location of Rag-i Bibi are mobilized to offer a perspective that characterizes this relief as the product of Sasanian Persia and the local artistic traditions of Bactria, actively designed to appeal to a diverse audience. This perspective builds upon previous readings of Rag-i Bibi as a conventional marker of political power, arguing instead for its role as mediating between local, regional, and international audiences.